Cleaner production approaches in drilling-fluids engineering / Uma Magesan Ulakanathan - Uma Magesan, Ulakanathan (2021)
Drilling-fluids or “mud”, as commonly known in the oil and gas industries, are very instrumental from the early stage of spudding to the completion phase of a well development. Currently, majority of the drilling-fluids utilized are either water-based which is prepared by mixing various types of chemicals on the offshore drilling rig itself, or synthetic oil-based which is recycled from previous drilling campaign. Drilling-fluids residues from dead volume of mud tanks, drilled cuttings and contaminated drilling-fluids from various operations are usually discharged directly to the sea. In addition, many of the support operations and practices in managing drilling fluids are less environmentally friendly. These practices may cause seawater pollution, which is hazardous to the micro aquatic life and overall marine environment. Therefore, in this study, an overall assessment was conducted for the full life cycle of drilling-fluids management to identify possible greening opportunities using cleaner production strategy. Subsequently, cleaner production (CP) options were generated and evaluated in the perspective of carbon footprint. From this initiative, a general guideline that can be used to green drilling-fluid related operations were developed in order to reduce contamination of marine environment. To meet the objectives, a CP audit was conducted in an offshore rig site which was executing a drilling operation from top section to reservoir section. Based on the analysis, carbon footprint could be reduced from 48.0 kg to 39.3 kg of carbon dioxide (CO2) / footage drilled with all the CP options proposed in all four intervals. This is equivalent to 18.2 % of reduction from total of 520.9 MT CO2 emitted throughout the drilling operations without considering any CP strategies. ii Meanwhile, batch drilling technics could be considered as the finest CP option among all. The contribution of batch drilling can be significantly observed via optimization of fluids volume and materials in first and fourth interval.